Assessment of forms finding of Chernobyl radionuclides in bottom sediments of cooling pond of the ChNPP - V. P. Protsak; О. О. Odintsov (Ядерна фізика та енергетика)
Assessment of forms finding of radionuclides 90Sr, 137Cs, 238Pu, 239,240Pu, 241Am and dispersal composition of fuel particles in bottom sediments of cooling pond of the ChNPP is carried out. According to the results of re-search in the year of 2012 more than 98 % of radionuclides in bottom sediments were in non-exchange (ex-changeable) state, while in the composition of the fuel particles can be contained about 70% 90Sr and more than 80 % 241Am and of the plutonium isotopes. Obtained results indicate the selective leaching of radionuclides from the matrix of fuel particles.